The Paternal Experience of Fear of Childbirth: An Integrative Review - Moran, Emma (Int J Environ Res Public Health, 2021)
Background: It is estimated that approximately 13% of expectant fathers experience a pathological and debilitating fear of childbirth. Objective: The aim of this integrative review was to examine and synthesise the current body of research relating to paternal experience of fear of childbirth. Methods: A systematic literature search of five databases—CINAHL, Cochrane Library, MEDLINE, PsycArticles and PsycInfo—identified seventeen papers. Methodological quality of studies was assessed using the Crowe Critical Appraisal Tool. Results: Thematic data analysis identified three themes: the focus of fathers’ childbirth-related fears, the impact of fear of childbirth on health and wellbeing, and fear of childbirth as a private burden. Discussion: Fear of childbirth is a significant and distressing experience for expectant fathers who may benefit from an opportunity to express their childbirth-related fears in an environment where they feel validated and supported. Antenatal education is recommended to enhance fathers’ childbirth-related self-efficacy to reduce fear of childbirth. Conclusions: Fear of childbirth may negatively impact the lives of men and consequently their families. Further investigation into methods and models for identifying and supporting men at risk of or experiencing fear of childbirth is required to improve outcomes for this population of men.